Odpowiedzi

2010-03-07T19:12:35+01:00
A) 3(x^-2x+3)-2 (x^-5x-1)= ? dla x = 2

3(x² -2x +3) -2(x² -5x -1) =
= 3x² -6x +9 -2x² +10x +2=
= x² + 4x +11

= (2)² + 4*2 +11=
= 4 + 8 +11=
= 23

b) a (2ab + b) -b ( a-2 ab + a^) = ? dla a=0,1 i b=(-10)
2a²b +ab -ab + 2ab² - a²b=
= a²b + 2ab²=
= ab(a + 2b)
= 0,1*(-10)*[ 0,1 + 2*(-10)]=
= -1*[ 0,1 - 20]=
= (-1 )*(-19,9)=
= 19,9
2010-03-07T19:15:01+01:00
3(x² -2x +3) -2(x² -5x -1) = 3x² -6x +9 -2x² +10x +2= x² + 4x +11= (2)² + 4*2 +11= 4 + 8 +11= 23

masz a) . chyba dobrze :)
2010-03-07T19:22:28+01:00
A) 3(x^-2x+3)-2 (x^-5x-1)= ? 2 do kwadratu = 4
3(4 - 4 +3) - 2(4 - 10 - 1) = 3*3 - 2 *(-7) = 9 + 14 = 23 * = razy








mam nadzieję,że mogłam pomóc